Consumer Protection in E-Commerce Transactions through Shopee Application according to Sharia Economic Law - Fadlurrahman, Iman; Fikrianihayah, Azzahra Nurul (Al-Muamalat: Jurnal Ekonomi Syariah, 2022)
The development of technology is increasingly rapid, there is a change in life, and buying and selling have turned online. One of the most popular e-commerce transactions in Indonesia is Shopee. The concept of Shopee e-commerce transactions is the same as bai 'salam. In e-commerce transaction activities, consumers can only see goods from the catalog, so there are often problems that harm consumers and the need for consumer protection. This study aims to determine consumer protection efforts in Shopee e-commerce transactions and how to review Islamic economic law on consumer protection in Shopee e-commerce transactions. This research method is a descriptive analysis by describing an event to be studied. The results of this study conclude that (1) Consumer protection efforts in Shopee e-commerce transactions have been regulated in the terms of service with the application of consumer protection for Shopee e-commerce transactions trying to return goods and refunds. (2) Based on Islamic law, consumer protection in Shopee e-commerce transactions is appropriate, because it applies khiyar rights. The concept of khiyar that is appropriate in the application of e-commerce Shopee is khiyar requirements, khiyar disgrace, and khiyar ru'yah.